Blood-based biomarkers in mild behavioral impairment: an updated overview - Angelopoulou, Efthalia; Androni, Xenia; Villa, Chiara; Hatzimanolis, Alexandros; Scarmeas, Nikolaos; Papageorgiou, Sokratis (Frontiers in Neurology, 2025)
Identifying individuals at-risk for dementia is one of the critical objectives of current research efforts, highlighting the need for simple, cost-effective, and minimally invasive biomarkers. Mild behavioral impairment (MBI), characterized by the emergence of persistent neuropsychiatric manifestations in older adults, has attracted increasing attention as a potential early indicator of cognitive decline and dementia. A growing number of studies have recently begun to explore the relationship between MBI and several blood-based biomarkers associated with Alzheimer’s disease (AD) pathology, neurodegeneration, as well as systemic metabolic and inflammatory dysregulation. In this context, MBI has been associated with lower plasma Aβ42/Αβ40 ratio, higher plasma phosphorylated tau at threonine 181 (p-tau181), increased neurofilament light chain (NfL) levels, as well as disturbances in metabolic markers, including homocysteine, insulin and ferritin, suggesting a multifaceted neurobiological basis for this syndrome. These findings offer insights into the underlying pathophysiology of MBI, and connection between neuropsychiatric symptoms and progression of AD. In this narrative review, we aim to summarize and critically discuss the emerging literature evidence linking MBI to blood-based biomarkers, hoping to shed more light on MBI’s pathophysiology, its connection to AD-related neurobiology, as well as its potential practical utility for predicting cognitive impairment, guiding early interventions and managing the risk for dementia.